Thoracoscopic two-port treatment of two extralobar pulmonary sequestrations in the left thoracic cavity of a child: a case report - Zhao, Huashan; Zhao, Shumin; Zhai, Yunpeng; Guo, Rui; Shen, Gang; Xu, Hongxiu; Huang, Sai; Zhang, Shisong (Frontiers in Pediatrics, 2025)
Reports of bronchopulmonary sequestration in two or more locations within the ipsilateral thorax in children are rare. To date, only a few clinical reports have described thoracoscopic two-port treatment for external lobe bronchopulmonary sequestration. We performed thoracoscopic two-port surgery on a 7-month-old girl and identified two abnormal masses in the left thoracic cavity: one located in the upper hilum of the lung and the other on the surface of the lower diaphragm. Both masses were resected using two-aperture thoracoscopic surgery and were pathologically confirmed as extralobar bronchopulmonary sequestrations. Preoperative computed tomography (CT) only detected the lesions in the upper hilum of the lung, indicating that CT alone is insufficient to achieve a comprehensive and accurate diagnosis of the disease in similar cases. Therefore, the thoracoscopic two-port technique can better diagnose and treat these diseases.